Possibilities and utopia of geodetic information systems from the practicians’ point of view - Simon, Ernst F. (Geodesy and Cartography, 2012)
The author comes to the conclusion that the variety of terms and the differences in interpretation existing in geodetic information systems must be restricted, and that all those systems have to be classified as geodetic information systems which are based on uniform coordinates, fundamental importance being attached to the field of land cadasters, i e real estate property as the basic system. Instancing the simultaneous existence of systems in the historical development from the land tax register to a multipurpose register and the necessity of uniformity in surveying, not having been recognised in time, also with regard to the development of automation, the importance of a uniform geodetic information system is outlined on the basis of the land cadastre in the Federal Republic of Germany. Citing the building cadastre and the service line cadastre as examples, the author explains that it is impossible to carry out any necessary material developments in the absence of certain basic conditions. Realisation of geodetic information systems is subject to political motivation, a wide‐spread basic structure, classical protection of property and practical multipurpose use, all of them offering possibilities of interrelation. Möglichkeiten und Utopien geodätischer Informationssysteme aus der Sicht eines Praktikers Article in German. Geodezinių informacinių sistemų galimybės praktikų požiūriu Santrauka. Daroma išvada, kad turi būti apribota geodezinių sistemų terminų įvairovė ir skirtingas interpretavimas. Visos tokios sistemos turi būti suklasifikuotos pagal bendras koordinačių sistemas, daugiausia dėmesio kreipiant į j ų reikšmę žemės kadastrui. Pavyzdžiui, Vokietijos Federacinėje Respublikoje plečiant žemės taksacijos registrą iki daugiafunkcinio žemės registro tuo pačiu metu buvo taikomos ir kitos geodezinės sistemos. Taigi laiku nebuvo atkreiptas dėmesys į geodezinių matavimų vientisumą ir bendrumą bei būtinybę tobulinti automatizuotas matavimo sistemas. Pateikiama pavyzdžių iš miestų statinių kadastro ir sklypų ribų kadastro, kuriais įrodoma, kad neįmanoma atlikti miestų plėtros uždavinių nesant apibrėžtų pagrindinių s ąlygų. Taigi geodezinių informacinių sistemų plėtra tampa politinės motyvacijos objektu, plačia pagrindine ir iš esmės daugiatiksle struktūra, klasikiniu nuosavybės apsaugos garantu. Raktažodžiai: geodezinės informacinės sistemos, žemės kadastras, pastatų kadastras. First published online: 03 Aug 2012